Az új vallási közösségek viszonya a társadalomhoz nyitottság, zártság, vonzerő néhány új vallási közösség tagjainál - Máté-Tóth András (Vallás a társadalomban = Religion in society, 2008)
When we analyse the relation between a social group and the society, our results primarily depend on the society perception we have. Taking the homogenous society as basis, every relation between every social group and the society is interpreted in a dichotomous (bipolar) model, due to the logical pressure. The whole of society is on one side, the social group is on the other side. This schematic model dominates every description. However, in the view of society, which takes the complex relation of many social subsystems into consideration, social groups also have a complex system of relations, the description of which are dominated by nuances. The classics of the sociology of religion like Max Weber, Ernst Troeltsch, Emile Durkheim and others, started from the homogenous view of society when describing churches and sects, as a result of which, society is opposed by the church or the sect. We analyse this relation in our study.